BOARD GENDER DIVERSITY MODERATES CAPITAL STRUCTURE, MANAGERIAL OWNERSHIP, AND FINANCIAL PERFORMANCE IN INDONESIAN CONSUMER FIRMS - Nita Wahyuni; Vinola Herawati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study aims to demonstrate how gender diversity can mitigate the impact of capital structure and managerial ownership on financial performance. The research sample consisted of 180 companies from the consumer cyclical and non-cyclical sectors listed on the Indonesia Stock Exchange in 2023. The data were analyzed using Moderated Regression Analysis (MRA), with firm age and size as control variables. The findings demonstrate that gender diversity significantly moderates the detrimental effects of capital structure and managerial ownership on financial performance. Capital structure negatively affects financial performance, while managerial ownership does not have a positive effect. These findings theoretically contribute to the application of stakeholder theory creating corporate value and highlight the strategic role of gender diversity and the significance of corporate capital structure management in enhancing financial performance